PENGARUH HARGA, KUALITAS, PROMOSI DAN PELAYANAN TERHADAP PERILAKU KONSUMEN DALAM PEMBELIAN KARTU XI BEBAS DI KOTA MAGELANG - Kurnia, Marlina` (Jurnal Analisis Bisnis Ekonomi, 2008)
Behavior of consumer is process passed by organization or someone in searching, esing, evaluating, and throwing away service or product after consumed to fulfill requirement of him. In this time many companies which producting card of prabayar so that in concurrence to compete to fight over consumer and market. Research of this aim to know influence of price, quality of, promotion and service to behavior of consumer in purchasing of card of XL free. Method intake of sampel is Accidental Sampling. Analyzer which used in this research is validity test and of reabilities, doubled linear regresi, test of F and test t. Examination result indicate that there are influence by simultan from free variable consisting of price (X1), quality of (X2), promotion (X3), and service (X4) to variable tied that is behavior of consumer (Y) that is F count/calculate > f value of is tabels of (10.741 > 2.579). To test R2 with value of adjusted R2 0.57. The value have the meaning of that free variable (X) have influence equal to 57% to variable tied Behavior of Consumer (Y). While the rest equal to 43% influenced by other variable. For the best of parsial (test t) obtained result of that by parsial there ate influence by selves from free variable to variable tied. This matter can bee seen from result test obtained t start from price variable (3.526), quality (3.133), promotion (2.293), and service (3.103) all more that t tables of equal to 2.0141. For the examination of variable having an effect on most dominant that is price variable. Because owning value of Standardized Coefficient (Beta) the biggestness compared to other variable.